2015
DOI: 10.1111/tbed.12332
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Brucellosis in Cattle, Goats and Humans in Rural Uganda: A Comparative Study

Abstract: A cross-sectional study was conducted to determine the presence of brucellosis in cattle, goats and humans in farms from south-western Uganda and identify risk factors associated with brucellosis in these three host groups. Data and serum samples were collected from 768 cattle, 315 goats and 236 humans, with 635 samples of bovine milk, from 70 farms in two different study areas in south-western Uganda. Sera from livestock were tested with the Rose Bengal Plate test, using B. abortus and B. melitensis antigens,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
4
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 53 publications
(80 reference statements)
6
35
4
7
Order By: Relevance
“…Among the bacterial diseases of cattle, mastitis was the most frequently diagnosed disease ( Table 3 ), this was in agreement with previous studies [16] , [17] that reported a prevalence of over 50%. Brucellosis was also frequently diagnosed at CDL (23%), consistent with earlier reports [18] , [19] , [20] , [21] . Nutritional diseases were more frequently diagnosed in chicken compared to cattle.…”
Section: Discussionsupporting
confidence: 90%
“…Among the bacterial diseases of cattle, mastitis was the most frequently diagnosed disease ( Table 3 ), this was in agreement with previous studies [16] , [17] that reported a prevalence of over 50%. Brucellosis was also frequently diagnosed at CDL (23%), consistent with earlier reports [18] , [19] , [20] , [21] . Nutritional diseases were more frequently diagnosed in chicken compared to cattle.…”
Section: Discussionsupporting
confidence: 90%
“…Brucella melitensis (B. melitensis) and Brucella abortus (B. abortus) tend to infect small ruminants and cattle respectively, causing abortions and infertility [2], resulting in huge economic losses. These animals are the most common source of human brucellosis, a debilitating chronic condition which when left untreated can lead to permanent sequelae [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the Brucella seroprevalence at dairy herd level ranged between 28 and 44% (911) and that antibodies against Brucella spp. were present in 11 and 40% of samples of bulk milk (12).…”
mentioning
confidence: 99%